An Apology for the Life of Mr. Colley Cibber, Volume 2 (of 2) : Written by Himself. A New Edition with Notes and Supplement - Cibber, Colley, 1671-1757 (Salt Lake City, UT : Project Gutenberg, 2013)
"An Apology for the Life of Mr. Colley Cibber, Volume 2 (of 2)" by Colley Cibber is an autobiographical treatise written in the early 18th century. This work serves as both a memoir and a reflective account of the author$1 (Bs experiences in the English theatre, particularly focusing on its practices, challenges, and evolving nature during his career. Cibber, himself a playwright and actor, recounts his journey, details interactions with notable figures in theatre, and sheds light on the management of theatrical companies. The opening of this second volume presents a vivid exploration of the theatre scene in Cibber's time, as he discusses the restructuring of actors and plays within various theatres, particularly the Hay-Market and Drury-Lane. He describes the dynamics of actor management, competition, and audience reception, highlighting how financial pressures influence theatrical quality and organization. Cibber expresses concerns over the evolving standards and the patronage of the stage, capturing both the enthusiasm and the turmoil that characterized his career in theatre. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/An_Apology_for_the_Life_of_Colley_Cibber
Release date is 2013-10-29
E-text prepared by Jonathan Ingram, RSPIII, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Theater -- Great Britain -- History -- 18th century; Dramatists, English -- 18th century -- Biography; Theatrical managers -- Great Britain -- Biography; Cibber, Colley, 1671-1757; Actors -- Great Britain -- Biography